Unmaking the presidency : Donald Trump's war on the world's most powerful office - Hennessey, Susan 1985- (Farrar, Straus and Giroux, 2020)
"The extraordinary authority of the American presidency has no parallel in the democratic world. Today, that power rests in the hands of Donald J. Trump -- and rarely, if ever, has the nature of a president clashed more profoundly with that of the office. Unmaking the Presidency is the definitive account of the unprecedented confrontation between a man and the institution he has come to embody." -- Front flap